2011
DOI: 10.1080/02619768.2010.534980
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative continuing professional development (CPD) for teachers in Scotland: aspirations, opportunities and barriers

Abstract: This paper explores stakeholders' views on the desirability of collaborative continuing professional development (CPD) and examines potential barriers. It draws on two projects which each explore perceptions of CPD for teachers in Scotland. The data include interviews with key informants and with practising teachers as well as survey data from Year 2-6 teachers. Analysis of data reveals an aspirational view of collaborative CPD, yet some of the data also reveal a pragmatic, occupational approach to CPD where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 12 publications
3
50
0
7
Order By: Relevance
“…The structure encompasses the organisation of the activity such as 40 the duration of the activity, type of activity (such as network, mentoring, research, workshop …) and collective participation. The emphasis on collective participation echoes Fullan (2001) and Kennedy's (2011) view on the importance of collaborative PD for enhancing student outcomes. However the gap between theory and practice relating to collaborative PD may need to be explored, especially in the Irish context 45 where individual practice still reigns (O'Sullivan 2011; Eivers and Clerkin 2013).…”
Section: Aq4mentioning
confidence: 99%
“…The structure encompasses the organisation of the activity such as 40 the duration of the activity, type of activity (such as network, mentoring, research, workshop …) and collective participation. The emphasis on collective participation echoes Fullan (2001) and Kennedy's (2011) view on the importance of collaborative PD for enhancing student outcomes. However the gap between theory and practice relating to collaborative PD may need to be explored, especially in the Irish context 45 where individual practice still reigns (O'Sullivan 2011; Eivers and Clerkin 2013).…”
Section: Aq4mentioning
confidence: 99%
“…However, teachers also learn when they engage in and learn from everyday classroom practice (continuous experiential learning) (cf. Meirink et al 2009;Czerniawski 2013), when they collaborate with colleagues (Kennedy 2011;Little 2012) and from being part of a school system and its change processes (Hoban 2002). To understand teachers' professional learning goals as they emerge from their daily professional life and within their workplace setting, a situated enquiry is needed (Webster-Wright 2009).…”
Section: Teachers' Professional Learningmentioning
confidence: 99%
“…In this study it was revealed that according to participant pre-service teachers, a collaborative and informal learning climate in classrooms is yet to be created; these teaching conditions can increase opportunities for learning and can also add to the enjoyment of the activity (Kennedy, 2011). Results suggest that the presence of peers in classrooms during the teaching practices of pre-service teachers is encouraging, as is the presence of a mentor teacher in the class.…”
Section: Discussionmentioning
confidence: 76%